Faktor-faktor yang Memengaruhi Keputusan Petani dalam Mempertahankan Usahatani Padi di Desa Hegarmanah, Kecamatan Jatinangor, Kabupaten Sumedang - Sabrina, Hidni; Supyandi, Dika (Universitas Galuh, 2026)
Hegarmanah Village is the largest rice producer in the Jatinangor Sub-district due to its geographical characteristics that are well-suited for rice cultivation. Despite having favorable geographical features such as suitable soil types and supportive weather, the area is not formally designated for agricultural use but rather for non-agricultural purposes. This has led to a continuous annual decline in rice field area due to land-use conversion. This study aims to identify the factors influencing farmers’ decisions to sustain rice farming amid this phenomenon. A quantitative method was employed using multiple linear regression analysis. The results show that personal, social, economic, and physical factors collectively influence farmers’ decisions to sustain rice farming in Hegarmanah Village. Partially, personal factors (farming experience and personal motivation), social factors (family tradition), economic factors (demand, costs, and income), and physical factors (climate and soil characteristics) were found to have a significant influence on the decision to continue rice farming in Hegarmanah Village.